Respuesta :

Answer:

a = 2

b = 4

c = 8

Step-by-step explanation:

Remember the relationship:

[tex](a^{x})^{y} = a^{x*y}[/tex]

First, in "a" we have:

a) [tex]8^{1/3} = \sqrt[3]{8} = 2[/tex]

then in the next ones, we can use the result that we obtained in the part a:

b) [tex]8^{2/3} = (8^{1/3})^2 = (2)^2 = 4[/tex]

Now we can do exactly the same in c:

c) where first we need to know that:

2*2*2*2 = 4*4 = 16

then:

2^4 = 16

then:

[tex]\sqrt[4]{16} = 16^{1/4} = 2[/tex]

Now let's solve the problem:

[tex]16^{3/4} = (16^{1/4})^3 = (2)^3 = 2*2*2 = 8[/tex]

ACCESS MORE